Labor resources of rural territories: distribution by the type of economic activity - M. A. Rensh; V. S. Bober (Вестник Северо-Кавказского федерального университета)
The distribution of labor resources in rural areas is determined by a number of factors that affect the system of formation of human resources by types of economic activity. Labor resources, as a type of economic category, embody the economic relations that develop in society regarding the production, storage and redistribution of working capacity, which corresponds to their type of activity. This article discusses the distribution of labor resources of rural areas by types of economic activity. The practical basis of the study was data on the labor resources of rural territories distributed by types of economic activity of the Krasnodar Krai, Rostov Region, belonging to the Southern Federal District of the Russian Federation, as well as the Trans-Baikal Territory and Primorye, which are part of the Far Eastern Federal District. The study considers strengths, weaknesses, opportunities and threats.